2020
DOI: 10.1099/ijsem.0.004100
|View full text |Cite
|
Sign up to set email alerts
|

Description of Citrobacter cronae sp. nov., isolated from human rectal swabs and stool samples

Abstract: Nine independent Gram-negative bacterial strains were isolated from rectal swabs or stool samples of immunocompromised patients from two different wards of a university hospital. All isolates were phylogenetically analysed based on their 16S rRNA gene sequence, housekeeping gene recN, multilocus sequence analysis of concatenated partial fusA, leuS, pyrG and rpoB sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…However, in March 2012, we detected the first Citrobacter freundii strain harboring the same carbapenemase-encoding bla IMP-8 gene ( 19 ), approximately 2.5 years after the first P. aeruginosa bla IMP-8 gene had been detected. Shortly after, the carbapenemase was detected in Citrobacter cronae ( 20 ). Since bla IMP-8 is rarely encountered in Europe and Germany ( 21 , 22 ) and has not yet been detected in rectal screening swabs from patients submitted to our hospital for the first time, we hypothesized that horizontal gene transfer had occurred within bacterial strains circulating in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…However, in March 2012, we detected the first Citrobacter freundii strain harboring the same carbapenemase-encoding bla IMP-8 gene ( 19 ), approximately 2.5 years after the first P. aeruginosa bla IMP-8 gene had been detected. Shortly after, the carbapenemase was detected in Citrobacter cronae ( 20 ). Since bla IMP-8 is rarely encountered in Europe and Germany ( 21 , 22 ) and has not yet been detected in rectal screening swabs from patients submitted to our hospital for the first time, we hypothesized that horizontal gene transfer had occurred within bacterial strains circulating in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical settings, Citrobacter spp. isolates represent up to 6% of all isolated Enterobacteriaceae from clinical specimens [ 28 ]. Members of the genus Citrobacter are reported to associate with nosocomial infections for a high mortality rate [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…isolates can have chromosomal AmpC β-lactamases, as well as plasmid encoded carbapenemases, which results in ineffective of many antimicrobial agents for treatment [ 20 , 22 , 34 , 35 ]. C. cronae was identified as a new Citrobacter species from human stool samples very recently [ 28 ], the antimicrobial profiles of C. cronae are largely unknow. In this study, we first identified an AmpC β-lactamase encoding gene ( bla CMY-98 ) in C. cronae , which provides a glimpse of antimicrobial insight into this species.…”
Section: Discussionmentioning
confidence: 99%
“…isolates represent up to 6 % of all isolated Enterobacteriaceae from clinical specimens. [29] Members of the genus Citrobacter are reported to associate with nosocomial infections for a high mortality rate. [30] The Citrobacter genus is most closely related to Escherichia coli and Salmonella, and is divided into 11 different genomospecies.…”
Section: Discussionmentioning
confidence: 99%
“…isolates can have chromosomal AmpC β-lactamases, as well as plasmid encoded carbapenemases, which results in ineffective of many antimicrobial agents for treatment. [21,23,35,36] C. cronae was identi ed as a new Citrobacter species from human stool samples very recently, [29] the antimicrobial pro les of C. cronae are largely unknow. In this study, we rst identi ed an AmpC βlactamase encoding gene (bla CMY−98 ) in C. cronae, which provides a glimpse of antimicrobial insight into this species.…”
Section: Discussionmentioning
confidence: 99%